Diseño de un sistema de costos para la bloquera Nacevilla provincia de Cotopaxi, parroquia Tanicuchi durante el primer trimestre del año 2023 - Arias Casa, Blanca Cecilia (2024)
The project titled “Design of a cost system for the Nacevilla Block, Latacunga Canton, Cotopaxi Province”, aims to determine the production cost by identifying the cost elements, for the production of the 7cm, 10 cm and 15 cm block, that are required by customers. When calculated empirically, the sales price was reasonably unknown, as well as the profits generated by each one. A quantitative approach methodology was applied to carry out a descriptive, exploratory, documentary and field research. Various techniques were used, including interviews with the production manager, as well as a survey directed at workers. These methodologies provided detailed information on production costs. A production order costing system was implemented in a Microsoft Excel sheet. Regarding the cost elements, the real amount of the production of the block of 7 cm $0.08, 10 cm $0.13 and 15 cm with a value of $0.13 was obtained. The application of this systematization will allow The Block Company will have adequate control over the costs for production quickly and efficiently, in addition, pertinent information will be obtained for correct decision-making.